2016
DOI: 10.1016/j.micromeso.2016.04.026
|View full text |Cite
|
Sign up to set email alerts
|

Development of sepiolite/SiC porous catalytic filters for diesel soot abatement

Abstract: Sepiolite/SiC honeycomb monolith Catalytic honeycomb monolith Wall-flow filter Wall detail Wall detail Application as diesel soot catalytic filter 10 µ µ µ µm 10 µ µ µ µm

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…The porosity of the filters was tuned by the addition of pore-generating agents, i.e., organic materials whose combustion led to the formation of interconnected macro-pores. Active elements (Co, Ba, and K [35,36], or Co and Ce [36]) were dispersed either by incorporating them into the dough [35] or by successive impregnation [35,36]. This latter technique assured a good distribution of active elements on both external and internal pore surface and, at the same time, it avoided the exposure of the catalyst to the high calcination temperature needed to remove additives but causing potassium loss [35].…”
Section: Sic Grainmentioning
confidence: 99%
See 1 more Smart Citation
“…The porosity of the filters was tuned by the addition of pore-generating agents, i.e., organic materials whose combustion led to the formation of interconnected macro-pores. Active elements (Co, Ba, and K [35,36], or Co and Ce [36]) were dispersed either by incorporating them into the dough [35] or by successive impregnation [35,36]. This latter technique assured a good distribution of active elements on both external and internal pore surface and, at the same time, it avoided the exposure of the catalyst to the high calcination temperature needed to remove additives but causing potassium loss [35].…”
Section: Sic Grainmentioning
confidence: 99%
“…Finally, it is worth mentioning the works by Tuler et al [35,36] and Yang et al [37], where non-traditional substrates were used. Tuler et al prepared wall-flow filters starting from sepiolite [35], a type of low-cost natural clay, or sepiolite/SiC mixtures [36].…”
Section: Sic Grainmentioning
confidence: 99%
“…It was found that the monolith with 70% natural clay in its composition had similar characteristics to commercially available DPF monoliths. The pore size of the monolith has to be improved for better filtration efficiency [61].…”
Section: Other Techniques For Active Regeneration Of Dpfmentioning
confidence: 99%
“…Yao et al [26] carried out sequential acid-base composite modification of sepiolite to prepare SiO 2 -Mg(OH) 2 nanocomposites, which exhibited high removal efficiency toward Gd(III), Pb(II) and Cd(II). Sepiolite is a natural nanomaterial with a relatively stable structure and an excellent carrier for other nanoadsorbents [27,28]. Therefore, it can effectively inhibit the agglomeration of nanostructured Mg(OH) 2 .…”
Section: Introductionmentioning
confidence: 99%